173 The role of an intronic single nucleotide polymorphism within the dopamine receptor type-2 gene on pituitary prolactin protein expression in bulls. (28th November 2020) - DeCarlo, Andrea N; McCarty, Keelee J; Richey, Sarah K; Long, Nathan; Pratt, Scott
Abstract: Detrimental effects to male reproductive physiology have been observed due to changes in prolactin (PRL) serum concentration. Regulation of PRL by dopamine binding to the dopamine type-2 receptor (DRD2) is well defined and associations between male physiology and single nucleotide polymorphisms (SNPs) within the DRD2 gene have been observed. The objective of the study was to evaluate association of a DRD2 SNP to PRL protein expression in bulls. Testis and epididymis were collected from bulls grazing a forage containing or lacking a dopamine agonist at the end of a 126 d study (n = 14). Bovine pituitaries (n = 587) were collected randomly over 3 mo from a local abattoir which processes cull cows and bulls. Sex of pituitaries was verified (n = 259 males) by duplex PCR for amplification of SRY and b-actin followed by Southern blotting of PCR products for selection of male. Prolactin protein expression was assessed in testis, epididymis, and pituitary by western blotting. Expression of PRL protein was below detection range in reproductive tissues but was present in pituitary, therefore experiments continued in pituitary. Restriction fragment length polymorphism genotyping was performed on pituitaries by amplification of the DRD2 SNP region followed by digestion with a Tfil enzyme. Digested of products produced 3, 2, or 1 band (AG, AA, GG, respectively). A subset of male pituitaries was blotted by slot blot manifold and PRL protein expression assessed by immunodetection and densitometry analysis normalized to GAPDH expression. Pituitary genotype distribution was 17.4% AA (n = 16), 63% AG (n = 58), and 19.6% GG (n = 18). Prolactin protein expression in the pituitary was similar across genotype (P = 0.23). These findings indicate that the DRD2 SNP has no genotypic effect on PRL protein expression in bovine pituitary.